Neoadjuvant chemoradiotherapy combined with immunotherapy for locally advanced rectal cancer: A new era for anal preservation - Wang, Yaqi; Shen, Lijun; Wan, Juefeng; Zhang, Hui; Wu, Ruiyan; Wang, Jingwen; Wang, Yan; Xu, Ye; Cai, Sanjun; Zhang, Zhen; Xia, Fan (Frontiers in Immunology, 2022)
For locally advanced (T3-4/N+M0) rectal cancer (LARC), neoadjuvant chemoradiotherapy (nCRT) followed by total mesorectal excision (TME) is the standard treatment. It was demonstrated to decrease the local recurrence rate and increase the tumor response grade. However, the distant metastasis remains an unresolved issue. And the demand for anus preservation and better quality of life increases in recent years. Radiotherapy and immunotherapy can be supplement to each other and the combination of the two treatments has a good theoretical basis. Recently, multiple clinical trials are ongoing in terms of the combination of nCRT and immunotherapy in LARC. It was reported that these trials achieved promising short-term efficacy in both MSI-H and MSS rectal cancers, which could further improve the rate of clinical complete response (cCR) and pathological complete response (pCR), so that increase the possibility of ‘Watch and Wait (W&W)’ approach. However, the cCR and pCR is not always consistent, which occurs more frequent when nCRT is combined with immunotherapy. Thus, the efficacy evaluation after neoadjuvant therapy is an important issue for patient selection of W&W approach. Evaluating the cCR accurately needs the combination of multiple traditional examinations, new detective methods, such as PET-CT, ctDNA-MRD and various omics studies. And finding accurate biomarkers can help guide the risk stratification and treatment decisions. And large-scale clinical trials need to be performed in the future to demonstrate the surprising efficacy and to explore the long-term prognosis.